Epiphyte assemblages of the Mediterranean seagrass Posidonia oceanica: an overview. (14th November 2015) - Piazzi, Luigi; Balata, David; Ceccherelli, Giulia
Abstract: This paper reviews the main studies dealing with epiphytes of both leaves and rhizomes of Posidonia oceanica, the main seagrass found in the Mediterranean Sea. A total of 660 epiphyte species has been recorded, including 430 on leaves and 437 on rhizomes. Of these, 205 are Rhodophyta, 59 Ochrophyta, 43 Chlorophyta, 78 Porifera, 82 Cnidaria, 19 Annelida, 155 Bryozoa and 19 Tunicata. The epiphyte assemblages demonstrate a gradient of dissimilarity from west to east, with the eastern area being the most unlike the others. The differences can be attributed mostly to rare species that differ amongst the Mediterranean regions. Many of the dominant taxa have been found in all meadows studied. Data concerning species composition, abundance, and patterns of spatial and temporal variability are summarized, and biotic and abiotic factors controlling the structure of assemblages are discussed. Responses of epiphyte assemblages to anthropogenic stressors, such as nutrient enrichment and biological invasions, are discussed in relation to the use of epiphytes as ecological indicators.